Changes in and Recognition of Electrochemical Fingerprints of Acer spp. in Different Seasons - Zhang, Pengchong; Li, Xiaolong; Zheng, Yuhong; Fu, Li (Biosensors (Basel), 2022)
Electroanalytical chemistry is a metrological analysis technique that provides information feedback by measuring the voltammetric signal that changes when a molecule is involved in an electrochemical reaction. There is variability in the type and content of electrochemically active substances among different plants, and the signal differences presented by such differences in electrochemical reactions can be used for plant identification and physiological monitoring. This work used electroanalytical chemistry to monitor the growth of three Acer spp. This work explores the feasibility of the electrochemical analysis technique for the physiological monitoring of highly differentiated plants within the genus and further validates the technique. Changes in the electrochemical fingerprints of A. cinnamomifolium, A. sinopurpurascens and A. palmatum ‘Matsumurae’ were recorded during the one-year developmental cycle. The results show that the differences in the electrochemical fingerprint profiles of Acer spp. can be used to distinguish different species and identify the growth status in each season. This work also concludes with an identification flowchart based on electrochemical fingerprinting.